Prison educators in the shadow of prison rules - Giovanni Torrente (Oñati Socio-Legal Series)
The essay presents the findings of a research study that investigated the legal and professional culture of prison officers responsible for supporting and rehabilitating inmates. The professional roles of educators, social workers, and experts in psychology and criminology were introduced into the Italian prison system following the reform of 1975 and subsequent amendments. Nearly 50 years after the reform came into effect, numerous questions remain open regarding the impact within the Italian prison system. Specifically, the research sought to determine to what extent these experts have influenced the professional culture and the culture of punishment among prison actors in Italy. Furthermore, more generally, the study questioned the impact of these roles on Italian prison practices. The results stem from three distinct periods of direct and participant observation during which the researcher served as a prison educator at a Northern Italian prison. The qualitative data collected suggest that treatment officers have only partially influenced the professional culture of other prison actors. Moreover, there appeared to be limited ability to alter the daily practices of the prison. Instead, these officers seem to have been profoundly influenced by the prison environment, which has facilitated the development of at least three critical issues addressed in the text: bureaucratization, defensive behaviour, and adherence to a punitive culture.